Improved sufficient conditions for monotonic piecewise rational quartic interpolation - Abd Rahni Mt Piah,; Unsworth, Keith (Universiti Kebangsaan Malaysia, 2011)
In 2004, Wang and Tan described a rational Bernstein-Bézier curve interpolation scheme using a quartic numerator and linear denominator. The scheme has a unique representation, with parameters that can be used either to change the shape of the curve or to increase its smoothness. Sufficient conditions are derived by Wang and Tan for preserving monotonicity, and for achieving either C1 or C2 continuity. In this paper, improved sufficient conditions are given and some numerical results presented.